Access to IoT Technologies for Processing and Sharing Terrestrial Biodiversity Data for Sustainable Livelihoods among Rural Communities in Turkana County, Kenya - Onunga, Jeremiah Osida; Ikoha, Anselemo Peters; Akwee, Peter Edome (International Journal of Computing Sciences Research; Vol 7 (2023): Volume 7, 2023)
Purpose – This study aimed to evaluate the access to IoT devices and technologies in Turkana County, Kenya, to enhance sustainable livelihoods. Method – The study used theoretical research findings to connect IoT theory and practice, as well as biodiversity data for sustainable livelihoods. The mixed method was used, with a sample of 384 households. Data was collected through questionnaires, Focus Group Discussions, and Key Informant Interviews. Results – The study found that rural communities in Turkana County primarily use mobile phones and radio for accessing terrestrial biodiversity data. The findings emphasized the need for initiatives allowing rural populations to fully utilize IoT technologies for processing and sharing terrestrial biodiversity data. Conclusion – The study's knowledge contribution took the form of an enhanced Sustainable Livelihoods (SLF), where varied responses and systematic analysis made terrestrial biodiversity data access and use via IoT relevant for understanding the relationship between terrestrial biodiversity data and sustainable livelihoods. Recommendations – The findings can be used to provide policy recommendations and suggestions for Kenya's future terrestrial biodiversity data plans, policies, and strategies. Implications – As IoT technologies continue to advance, their potential for positively impacting biodiversity conservation and environmental management will only grow, ensuring a brighter future for our planet's ecological health.